Case Report: Simultaneous pancreas–kidney transplantation in MELAS: first reported case with 5-year follow-up - Nilsén, Vera; Bojstedt, Julia; Nordström, Johan (Frontiers in Transplantation, 2026)
BackgroundMitochondrial encephalomyopathy with lactic acidosis, and stroke-like episodes (MELAS) is a rare mitochondrial DNA disorder that, in severe cases, can result in insulin-dependent diabetes and end-stage renal disease (ESRD). While organ transplantation is a potential treatment, documented cases remain scarce.MethodsA 40-year-old patient with dialysis-dependent ESRD and diabetes secondary to MELAS underwent simultaneous pancreas-kidney transplantation. The perioperative and postoperative periods were uncomplicated with only targeted MELAS-specific adaptations to standard protocols.ResultsDuring the 5-year follow-up, the patient maintained excellent kidney allograft function and sustained insulin independence, with no need for dialysis or exogenous insulin therapy. At 5 years, creatinine was 77 µmol/L with an estimated GFR above 90 mL/min/1.73 m2, and glycated hemoglobin was 40 mmol/mol.ConclusionsSPK transplantation may be feasible in carefully selected patients with MELAS, ESRD, and diabetes, providing durable renal and metabolic graft function at 5 years. To our knowledge, this is the first reported SPK case in MELAS, with extended follow-up.